2010
DOI: 10.1016/j.jvs.2010.02.263
|View full text |Cite
|
Sign up to set email alerts
|

Classification of proximal endovenous closure levels and treatment algorithm

Abstract: A classification system for saphenous endovenous closure which extends above the epigastric vein has been helpful in guiding management. A GSV diameter at the SFJ of >8 mm and a history of DVT results in significantly higher rates of proximal thrombus extension into the femoral vein. A short course of LMWH, until clot retracts back into the saphenous vein, is therapeutic. Management of the patients with thrombus flush with the femoral vein wall still needs to be defined, but the outcome from these patients is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 7 publications
3
72
2
2
Order By: Relevance
“…16 Similar to our prior analysis of the GSV, segmental thermal ablation of the SSV resulted in immediate resolution of saphenopopliteal reflux with high vein closure rates in the majority of patients who underwent treatment across a wide range of CEAP classes. In fact, our patient population in this study trended toward more severe chronic venous insufficiency than similar published series.…”
Section: Discussionsupporting
confidence: 72%
“…16 Similar to our prior analysis of the GSV, segmental thermal ablation of the SSV resulted in immediate resolution of saphenopopliteal reflux with high vein closure rates in the majority of patients who underwent treatment across a wide range of CEAP classes. In fact, our patient population in this study trended toward more severe chronic venous insufficiency than similar published series.…”
Section: Discussionsupporting
confidence: 72%
“…Consequently, we try to identify all incompetent superficial and perforating veins that might be contributing to ambulatory venous hypertension and attempt to correct the incompetence with ablation of refluxing veins. Due to the high success of ablation of saphenous veins and other axial veins, which in our experience is Ͼ99%, 15 we correct them first. We also ligate or perform microphlebectomy on incompetent tributary veins that reflux into the area of the ulcer, although we are reluctant to make incisions into skin with lipodermatosclerosis, since wound healing can be a problem.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies by Lawrence et al 14 reported closure rates of 99.6% for CTP between 2.0 and 2.5 cm from the SFJ among 500 patients. Thirteen patients (2.6%) experienced thrombus extension into the femoral vein or adherent to its wall, which was treated with anticoagulation.…”
Section: Discussionmentioning
confidence: 99%